(untitled) (Bangladesh Agronomy Journal, 2019)
The experiment was conducted at the research field of the Agronomy Division, Bangladesh Agricultural Research Institute (BARI), Bangladesh during rabi season of 2017-2018 to evaluate the flowering behavior and pod yield of French bean. Three varieties namely BARI Jharsheem-1, BARI Jharsheem-2 and BARI Jharsheem-3 were sown on 30 November, 15 December and 30 December, respectively for getting temperature variation. Sowing dates based on temperature variation, significantly affect the flowering behaviour and pod yield of French bean varieties. Developmental events were badly affected when sown on 30 December. Crop accumulated lower GDD for different development events when sown late. Flowering duration of 30 November sowing were longer due to prevailing low temperatures (Min.10.3-11.4 °C and Max 23.7-24.5 °C) (Table 2). On the contrary, minimum flowering duration was recorded in 30 December sown crop (11-17 days). Minimum duration might be due to prevailing high temperature (Min.14.9-15.3 °C and Max 27.6-28.8 °C) that shorten the flowering duration of all French bean varieties. Pod yield of all the varieties were more at November sowing and decreased towards late sowing. November 30 sowing performed better in relation to yield components and yield which was very close to 15 December sowing. BARI Jharsheem-1 produced the highest pod yield (16.77t ha-1) in 30 November sowing. French bean had been sown on November to December showed the greater variability in respect of ﬂowering, ﬂowering duration and the number of pods. The results revealed that November would be the optimum sowing date (15 Nov.-30 Nov.) for maximum pod yield of french bean var. BARI Jharsheem-1 Bangladesh Agron. J. 2018, 21(2): 25-32